Freedom of religion in the 21st century : a human rights perspective on the relation between politics and religion - Ziebertz, Hans-Georg, 1956- (Empirical Research in Religion and Human Rights, 2015)
Freedom of religion consists of the right to practice, to manifest and to change one's religion. The modern democratic state is neutral towards the variety of religions, but protects the right of citizens to practice their different religious beliefs. Recent history shows that a number of religious claims challenge the neutral state. This happens especially when secularity is rejected as the basis of the modern state. How can conflicting interpretations of the relation between religion and state be balanced in our world? This book reflects on conflicts that seem to be implied in the freedom of religion, on its causes and how they can be overcome. Contributors are: Katajun Armipur, Ernst Hirsch Ballin, Ian Cameron, Susanne Döhnert, Leslie Francis, Carsten Gennerich, Handi Hadiwitanto, Mandy Robbins, Prof. Hans Schilderman, Stefanie Schmahl, Carl Sterkens, Alexander Unser, Johannes A. van der Ven and Hans-Georg Ziebertz.